Prevalence of Anti-JC Virus Antibody in Multiple Sclerosis Patients in Kuwait. (22nd January 2014) - Lamdhade, S.; Ashkanani, A.; Alroughani, R.
Abstract : Background . Multiple sclerosis (MS) therapeutics entered a new era after the development of anti-JC virus (anti-JCV) antibody assay that assesses the risk of development of progressive multifocal leukoencephalopathy (PML) in patients treated with natalizumab. Objective . To determine the prevalence of anti-JCV antibody among MS patients in Kuwait. Methods . Using the national MS registry, demographics and disease characteristics of MS patients who were screened for anti-JC virus antibody were collected. The prevalence of anti-JCV antibody seropositivity and its association with demographic and disease characteristics were evaluated. Results . Out of 110 screened MS patients for anti-JCV antibodies, 65.5% were females. Mean age and disease duration were 29.23 ± 8.55 and 5.39 ± 5.04 years, respectively. 47.3% of patients were already on natalizumab and 52.7% of patients were screened for stratification to either natalizumab or a different Disease Modifying Therapy (DMT). The overall prevalence of anti-JC virus antibody was 40%. Gender (P = 0.69 ), disease duration (P = 0.11 ), and number of natalizumab infusions (P = 0.64 ) were not associated with seropositivity. Patients aged ≥30 years were more likely to be seropositive (P = 0.01 ). Conclusion . The prevalence of anti-JCV antibody is slightly lower than what is reported in published studies. Seropositivity was associated with an increasing age of MS patients.